Uji Instrumen Motivasi Pengidap Hiv/Aids Rumah Cemara Bandung - Megia Erida (Peneliti.net, 2021)
This study aims to examine the motivation questionnaire for people with HIV / AIDS from futsal sports activities at Rumah Cemara Bandung. The research was conducted using the descriptive survey method. Sampling in this study using incidental sampling technique. The sample in this study amounted to 10 people who were positive with HIV / AIDS. The instrument used was a closed questionnaire using a Likert scale. This questionnaire covers five human needs, namely; Physiological Needs, Safety and Security Needs, Affiliation or Acceptance Needs, Self Actualization Needs and Appreciation Needs. Based on these human needs, the researcher needs to test the validity of the questionnaire, there are 41 question statements. By using the validity and reliability test, it can be concluded that the questionnaire items are declared valid if the value of r table is more than r table (r count <r table) based on the results of calculating the validity of the invalid questionnaire consisting of 12 and valid 29 stated that it can be used as a measuring tool with the reliability test results of 0.77, the reliability is high. The existence of this questionnaire test provides evidence of support for future research examining the motivation of people with HIV/AIDS.